Scientific research and investments investments in the region scientific and practical base of the country - Rasulov Khurshid Kakhkhorovich (THE INNOVATION ECONOMY, 2026)
The article examines the scientific and practical aspects of fostering investment growth in the agricultural sphere of the Kashkadarya region. It analyzes the scale and impact of capital inflows into sectors such as cotton production, grain farming, fruit and vegetable cultivation, and livestock. The research highlights the socio-economic benefits attained through these investments, while also discussing barriers such as water resource constraints, infrastructure limitations, and lagging technological adoption. The paper presents a set of proposals aimed at enhancing the investment environment, promoting sustainable technologies, and strengthening agricultural development.